Studi Komparasi Keterampilan Proses Sains Mengunakan Model Pembelajaran Inkuiri Terbimbing dengan Model Pembelajaran Inkuiri Terstruktur Materi Termokimia pada Siswa Kelas XI MIPA SMAN 1 Gerung Tahun Ajaran 2017/2018 - Sukarni Sukarni; Aliefman Hakim; I Nyoman Loka (Indonesian Publication Center, 2019)
The research aims to know are there or not differences between student who use guided inquiry learning model and student who use structured learning model on thermochemistry at class XI science of SMAN 1 Gerung for academic year 2017/2018. This research is quasi-experimental with deign using nonequivalent control group design. The sample was taken using purposive sampling technique with class XI MIPA 3 as experiment I class and class XI MIPA 2 as experiment II. The writer took the data using instrument which was science process skill test and observation sheets. Hypotheses test using t-test at significances level of 5%. Calculating data using t-test from posttest value between the two class experiment, obtained the value of t-count was 6,10 and t-table is 2,00, while calculating data using t-test from observation value between the two class experiment obtained the value of t-count was 11,27 and t- table is 2,00. It mean that alternative hypothesis (Ha), which told the student teaching use structured inquiry model learning higher than student teaching use guided inquiry model learning on science process skill has been accepted.